Principal’s Strategy in Improving Educational Quality - Nurmawati, Nurmawati; Ahyani, Nur; Rohana, Rohana (Journal of Social Work and Science Education, 2023)
This qualitative study investigates the principal’s strategy in improving educational quality at SD Negeri 19 Gelumbang by using observations, interviews, and documentation. The results showed that the principal’s strategy includes empowering teachers’ competencies, and complete learning resource centers, working together to develop learning models, attempting to foster good cooperation with teachers and staff, and improving teachers’ discipline, including requiring teachers to participate in every school. The school environment at SD Negeri 19 Gelumbang is supportive of teaching and learning activities. The main source of strength is students’ eagerness to learn. Close family relationships among students are also practiced in the school environment.